(untitled) (Economic studies journal, 2021)
Abstract The study deals with the role of environmental auditing in predicting financial failure, and the problem of the study is is there a statistically significant relationship between the requirements of environmental auditing and forecasting financial failure? Is there a statistically significant relationship between the elements of the environmental review and the prediction of financial failure? Is there a statistically significant relationship between the scope of the environmental audit and the prediction of financial failure? The study aimed to identify the work requirements, scope and elements of environmental auditing, and then their contribution to predicting financial failure, and to achieving the objectives of this study and a solution to its problem. The two researchers formulated the hypotheses and there is a statistically significant relationship between the requirements of the environmental review and the prediction of financial failure, and there is a statistically significant relationship between the elements of the environmental review and the prediction of financial failure. There is a statistically significant relationship between the scope of the environmental audit and the prediction of financial failure The study concluded that the requirements and scope of the environmental audit help the management to predict financial failure. The study followed the historical approach, the deductive approach, the inductive approach and the descriptive analytical approach. The study recommended paying attention to environmental auditing and adopting sound methods to reach information that helps management predict financial failure before it occurs in the future, and enables management and investors to make rational investment decisions.